The Effect of Using Modified Plastic Ball Media on Improving Dribbling Learning Outcomes in Football for Fifth Grade Students at SD Negeri 094166 Sidotani I Bandar - Siahaan, Miduk Putra; Tantri, Afri (Educational Sciences Journal, 2025)
This study aims to determine the effect of using modified plastic ball media on improving dribbling learning outcomes in football among fifth-grade students at SD Negeri 094166 Sidotani I Bandar during the 2021/2022 academic year. The research employed a quasi-experimental method conducted both on the field and in the classroom. The population consisted of 30 students from Grade V, all of whom were selected as the research sample. Data collection was carried out through dribbling tests using the inner and outer sides of the feet, evaluated with a performance rubric. Data were analyzed using t-test statistics to assess the effect of the independent variable. The results showed an increase in the average score from the pre-test (8.13) to the post-test (9.40), with a difference of 1.27 points. However, the independent sample t-test revealed that the result was not statistically significant (sig. (2-tailed) = 0.260 > 0.05), indicating that the hypothesis was rejected. Therefore, it can be concluded that the use of modified plastic ball media did not have a significant effect on improving dribbling learning outcomes in football for the students of SD Negeri 094166 Sidotani I Bandar.